Corporate Venture Capital in the Digital Age - Ademi, Petrit; Justus Liebig University Giessen (My University, 2022)
This doctoral thesis examines the phenomenon of corporate venture capital (CVC) in the digital age. Through three empirical studies, this thesis analyzes the integration, evaluation, and instigation activities of CVC investors under the consideration of the peculiarities that characterize the digital age. Drawing upon qualitative research, a conjoint experiment, and a longitudinal approach, this thesis derives important implications for theory and practice related to CVC investing, (corporate) entrepreneurial decision-making, the role of affordances for inter-organizational partnerships, and the characteristics of digital technologies for entrepreneurial activities.
Keywords: ddc:650